TIPOLOGI FATWA DI ERA MODERN: DARI OFFLINE KE ONLINE - Azhari, Rusli (Hunafa: Jurnal Studia Islamika, 2011)
Abstract: This paper deals with the typology of fatwÄ (Islamic legal opinion) in a contemporary era. It is assumed that change of paradigm will give an impact to changes in knowledge and its media of transmision. This also applies to fatwÄ. Due to this change of paradigm, fatwÄ has also undergone changes either in content or media of transmission. In this globalization era, which is characterised with the advance of information technology, fatwÄ can be divided into such categories as state, personal, individual, collective, and online fatwÄs. These fatwa models have their own unique characteristics in terms of ideologies, interests and scope of transmission.Kata Kunci: Internet, fatwa online, mufti negara, mufti personal